NEW RECORD OF Mycena chlorophos (BIOLUMINESCENT FUNGI) FOR INDONESIA - Fathansah Nugeraha; Silva Ristiana Haryadi; Wahyu Aji Mahardhika; Oktan Dwi Nurhayat; Ivan Permana Putra (SEAMEO BIOTROP, 2025)
HIGHLIGHTS- Glowing mushrooms were found at night in the forest of IPB University and showed a bright green light in the dark.- Examination of their morphological features and phylogeny material confirmed they are the species Mycena chlorophos.- This is the first confirmed record of Mycena chlorophos in Indonesia, extending its known distribution worldwide. ABSTRACTA bioluminescent fungus produce light as a result of a chemical reaction within its body. The majority of fungi exhibiting bioluminescence are classified within the Mycenaceae which comprises a significant proportion of the known glowing fungi. One of those species which well noted worldwide is Mycena chlorophos. However, no clear record of M. chlorophos has been discovered in Indonesia. While engaging in our routine late-night mushroom foraging in IPB University Campus Forest (IPBUCF), some glowing basidiomata were encountered. This study sought to determine the taxonomic classification of the collected specimens through comprehensive morphological and molecular examinations. The fresh fruiting bodies were underwent thorough examination based on macroscopic and microscopic characteristics. Phylogenetic analysis of the rDNA-ITS region was conducted using ITS 1/2 primers, and the integration of morphological and molecular data verified that our specimens belong to Mycena chlorophos. By morphology, our specimen poses convex pileus with shallow depression at centre, viscid, shiny, adnexed lamellae with series of lamellae, ellipsoid and smooth basidiospores. The pileus and hymenophore glow vividly with a bright greenish hue in the darkness. The BLAST analysis indicated a 98% similarity between our specimen and Mycena chlorophos from China, ranking it among the top matches. Furthermore, the phylogenetic tree positioned our specimens within the M. chlorophos clade with a 100% bootstrap support value. Our specimen was in sub clade with materials from Malaysia. The DNA sequence of our scpecimen has been registered to Gen Bank and can be used for future reference of bioluminescent fungi wordlwide. This research updates information regarding the distribution and characteristics of M. chlorophos in Indonesia. The discovery of this species in the IPBUCF adds to the known geographical range of M. chlorophos near the anthropogenic activity in Indonesia. In addition, our result also contributes to the growing documentation of bioluminescent fungi in Indonesia, a region with high but underexplored fungal biodiversity.